The main medical problems of ostriches - KRITAS (Σ.Κ. ΚΡΗΤΑΣ), S. K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Ostrich raising became recently a novel and seemingly profitable type of farming in Greece, and many other European countries. This review presents several medical conditions that may be observed during veterinary practice in these farms, or that may be imported in Greece by newly bought reproductive stock. An attempt was made to present ostrich diseases according to the principally affected organic system (digestive, respiratory, nervous, myoskeletal, reproductive etc.).